2022
DOI: 10.3390/ijerph192315870
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Professionals’ Views and Perspectives towards Aging

Abstract: Improving care for the older population is a growing clinical need in the United States. Ageism and other attitudes of healthcare professionals can negatively impact care for older adults. This study investigated healthcare professionals’ (N = 140) views towards aging and characterized a confluence of factors influencing ageism perspectives in healthcare workers using path analysis models. These models proposed relationships between aging anxiety, expectations regarding aging, age, ageism, and knowledge. Aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Even today, with the dramatic increase in older people with multimorbidity, medical students and trainees have low interest in their needs or in geriatrics as a career [ 37 , 38 ]. The resulting lack of knowledge about ageing processes and needs of older people contribute towards ageism [ 39 ] and poor care for older adults. A recent systematic review has shown that the three underlying wishes regarding healthcare for people aged over 80 years are: feeling safe, feeling like a meaningful human being, and maintaining control and independence [ 40 ].…”
Section: What History Can Tell Us About the Presentmentioning
confidence: 99%
“…Even today, with the dramatic increase in older people with multimorbidity, medical students and trainees have low interest in their needs or in geriatrics as a career [ 37 , 38 ]. The resulting lack of knowledge about ageing processes and needs of older people contribute towards ageism [ 39 ] and poor care for older adults. A recent systematic review has shown that the three underlying wishes regarding healthcare for people aged over 80 years are: feeling safe, feeling like a meaningful human being, and maintaining control and independence [ 40 ].…”
Section: What History Can Tell Us About the Presentmentioning
confidence: 99%
“…Ageism, like disability, is primarily socially constructed (Butler, 1975), as are female body ideals that embrace youth (Sanberg, 2013). Ageism is the driver of unfair practices in the allocation of opportunities and resources (Palsgaard et al, 2022), which extend to health care and LTC in a youth-oriented culture (Carney & Gray, 2015). Research has also found that having an aged appearance has social and financial consequences.…”
Section: Theoretical Framework Feminist Disability Studiesmentioning
confidence: 99%
“…For example, older adults in institutional care could be assumed to be at fault for their increased need for assistance (Chrisler et al, 2016;Gibbons, 2016). Negative ageing attitudes not only make it easier for the perceiver to disregard the welfare and humanity of older adults but also impact older adults' physical and mental health and well-being (Bellingtier & Neupert, 2016;Chrisler et al, 2016;Palsgaard et al, 2022).…”
Section: Fdt and Cy In Long-term Carementioning
confidence: 99%
See 1 more Smart Citation